Rare Presentation of Liposarcoma in the Breast: A Case Report and Treatment Considerations - Chhabra Maninder K; Dogra Reetu; Sood Neelam; Chhibber Puneet (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Aim: We present a case of a breast lump that threw a histopathological surprise of liposarcoma after excision. Background: Liposarcoma of the breast is a rare entity accounting for 0.3% of breast sarcomas which in turn are responsible for less than 1% of breast malignancies. We present this case for rarity and for its being a histological surprise. Most of the liposarcomas are seen to arise in malignant phyllodes tumors. Because of the rarity of the disease, there are no randomized trials specifically addressing treatment modalities in breast sarcoma. Case Summary: We report a case of 60 60-year-old female presenting with a painless, progressively increasing lump in the right breast for 4 months. Examination revealed a 6*5 cm, firm, non-tender, mobile, lump with a smooth surface and clear margins in the right upper outer quadrant. Ultrasonography of breasts and mammography were suggestive of BIRADS III lesion. The results of the Trucut biopsy pointed to a fibroepithelial lesion with cellular stroma. An excision biopsy was performed, taking into account the patient’s age and the size of the lump. According to the histopathology report, the fibro cellular stroma is where liposarcoma originates. In the second stage, re-excision of the margins was performed as part of completion surgery. The patient was asymptomatic with no evidence of recurrence after 1.5 years of follow-up. Discussion: Most of the liposarcomas have been found to arise in malignant phyllodes tumors, as opposed to primary liposarcomas of the breast which arise de novo from fibro cellular stroma. Our case was liposarcoma of breast which was identified on histopathology after excisional biopsy and was managed well with re-excision of the margins as per NCCN guidelines. Conclusion: Liposarcoma of the breast is rare. It can present as a benign lesion clinically. Treatment is by wide local excision with tumour-free margins or re-resection of margins in case of a histological surprise.